Flood Frequency Analysis of Akçay Stream - Mehmet Sandalcı (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
It is extremely important to predict flood forecastsin planning water systems and reducing flood damage. For the Akçay stream,which is one of the important branches of the Sakarya river , the floodforecasts that can be seen at certain time frequencies have been estimated.Normal (Gauss), log-normal and Gumbel distributions have been estimated in thiscontext. The Kolmogorov-Smirnov test investigated the suitability of thedistributions and found that the log-normal distribution was appropriate. As aresult, the 100-year flood plain was found to be 7,52 m3/sec on log-normal distribution.